2018
DOI: 10.12659/msm.909469
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Resistin Levels in Patients with Acute Aortic Dissection: A Propensity Score-Matched Observational Case-Control Study

Abstract: BackgroundThe aim of this observational case-control study was to compare the levels of plasma resistin between patients with acute aortic dissection and matched controls, and to use propensity score matching (PSM) to reduce case selection bias and clinical confounders.Material/MethodsWith the use of PSM, this study included 43 pairs of patients with acute aortic dissection (type-A and type-B dissection) and matched controls. Plasma resistin levels and other laboratory parameters were compared between the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…AAD is a fatal cardiovascular disease [ 13 ]. Since the underlying mechanisms of the development and progression of spontaneous AAD cases remain unclear, a screening or prevention strategy for these patients has yet to be developed [ 14 ]. In previous studies, preoperative creatinine, uric acid, serum tenascin-C, and inflammatory factors were all associated with postoperative mortality following AAD [ 10 , 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…AAD is a fatal cardiovascular disease [ 13 ]. Since the underlying mechanisms of the development and progression of spontaneous AAD cases remain unclear, a screening or prevention strategy for these patients has yet to be developed [ 14 ]. In previous studies, preoperative creatinine, uric acid, serum tenascin-C, and inflammatory factors were all associated with postoperative mortality following AAD [ 10 , 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to strengthen our hypothesis, it is essential that we develop further/future studies on larger groups of patients. Also, they must include other markers of acute inflammation, with a special interest for those reportedly correlated with resistin during acute cardiovascular events: tumor necrosis factor α (TNF-α), interleukin-6 (IL-6), high-sensitivity C-reactive protein (hs-CRP) and other proinflammatory cytokines [34]. Resistin promotes the production of TNF-α, IL-1β, IL-6 and other cytokines [12,35].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that resistin can antagonize insulin to prevent cells from taking up glucose, resulting in decreased glucose tolerance in patients with T2DM, and that it can cause obesity by promoting blood sugar elevation and stimulating fat cell proliferation [115]. It is also involved in the inflammatory response, stimulating the release of endothelin-1 and monocyte chemotactic protein-1 by vascular endothelial cells, and promoting atherosclerosis, thereby leading to endothelial dysfunction [116,117]. While reducing weight and fat accumulation through exercise, which is an effective treatment for obesity and its complications, also has a positive effect on resistin concentrations, the relationship between the two is not clear.…”
Section: The Physiological Function Of Resistinmentioning
confidence: 99%